PENGARUH GERAK DAN LAGU TERHADAP KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN DI TK KARYA YOSEF PONTIANAK - Pricilla, Lea Dinda; Miranda, Dian; Amalia, Anisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the effect of motion and song on the kinesthetic intelligence of children aged 5-6 years at Karya Yosef Pontianak Kindergarten. This study uses an experimental, onegroup pretest-posttest methodology. The data source for this research is children aged 5-6 years at Karya Yosef Pontianak Kindergarten. The data collected in this study is data regarding kinesthetic intelligence obtained through observation. Data collection techniques were obtained through observation guidelines. The data analysis technique used to test the research hypothesis is the paired sample t-test. It is proven from the results of the t test, which is 0.000 alpha value (0.05) so the conclusion is to reject ð»0, which means that there is a real difference between the value of the child's kinesthetic intelligence at the time of the pretest and the value of the child's kinesthetic intelligence at the time of the posttest.